2000
DOI: 10.1021/jp002882u
|View full text |Cite
|
Sign up to set email alerts
|

51V MAS NMR Investigation of 51V Quadrupole Coupling and Chemical Shift Anisotropy in Divalent Metal Pyrovanadates

Abstract: Magnitudes and relative orientations of 51V quadrupole coupling and chemical shift tensors have been determined from 51V magic-angle spinning (MAS) NMR spectra at 14.1 T for seven divalent metal pyrovanadates:  α- and β-Mg2V2O7, Ca2V2O7, α-Zn2V2O7, Cd2V2O7, BaCaV2O7, and α-BaZnV2O7. This has been accomplished by least-squares fitting of the integrated spinning sideband intensities observed for the central and satellite transitions employing spectral widths up to 4 MHz. Numerical error analysis of the optimized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(103 citation statements)
references
References 37 publications
(100 reference statements)
6
96
1
Order By: Relevance
“…The MAS spectra are observed to break up into spinning sidebands (ssbs) and the absence of significant quadrupolar secondorder shifts indicates that the quadrupole coupling constant Q CC D e 2 qQ/h is moderate (jQ CC j < 3 MHz). 1,2,22,23 Indeed, the good agreement between the experimental and calculated data (Figs 1 and 2) demonstrates that the complete manifolds of ssbs from all seven 51 V transitions are detected. For simplicity, in Figs 1 and 2, the isotropic peak, determined from spectra employing different spinning speeds, was arbitrarily chosen as the chemical shift reference.…”
Section: Resultssupporting
confidence: 57%
“…The MAS spectra are observed to break up into spinning sidebands (ssbs) and the absence of significant quadrupolar secondorder shifts indicates that the quadrupole coupling constant Q CC D e 2 qQ/h is moderate (jQ CC j < 3 MHz). 1,2,22,23 Indeed, the good agreement between the experimental and calculated data (Figs 1 and 2) demonstrates that the complete manifolds of ssbs from all seven 51 V transitions are detected. For simplicity, in Figs 1 and 2, the isotropic peak, determined from spectra employing different spinning speeds, was arbitrarily chosen as the chemical shift reference.…”
Section: Resultssupporting
confidence: 57%
“…In pyrovanadates of divalent metals two vanadium atoms in V 2 51 V NMR parameters for many pyrovanadates of divalent metals have been reported by Nielsen et al [147].…”
Section: Tetrahedral Q 1 Sitesmentioning
confidence: 84%
“…and even several V-containing biological systems, have also recently been studied [93,94,[144][145][146][147][148][149]. It is noteworthy, that almost Table 4 Different types of vanadium sites all types of vanadium sites shown in Table 4 can be found in these individual compounds.…”
Section: Chemical Shielding and Quadrupolar Tensor Parameters In Indimentioning
confidence: 99%
“…catalysis [9] and electrochemistry [10]. Both monodimensional (MAS and SAtellite TRAnsition Spectroscopy, SATRAS) and two-dimensional (Multiple Quantum, MQMAS) experiments have been recently applied to the study of meta-, pyro-and ortho-vanadates [9,[11][12][13][14]. In particular, it has been shown that the NMR spectra of orthovanadates are dominated by electric quadrupolar interaction (the quadrupolar coupling constant, C Q ; spans between 1 and 6 MHz), whereas the chemical shift anisotropy (CSA) is less than 100 ppm, due to the almost spherically symmetric shielding tensor of the tetrahedral oxygen environment (Q 0 unit) [9,14].…”
Section: X-ray Powder Diffractionmentioning
confidence: 99%